2009
DOI: 10.1111/j.1472-4642.2008.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Threats and biodiversity in the mediterranean biome

Abstract: Aim  Global conservation assessments recognize the mediterranean biome as a priority for the conservation of the world's biodiversity. To better direct future conservation efforts in the biome, an improved understanding of the location, magnitude and trend of key threats and their relationship with species of conservation importance is needed.Location  Mediterranean‐climate regions in California‐Baja California, Chile, South Africa, Australia and the Mediterranean Basin.Methods  We undertook a systematic, pan‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
228
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(237 citation statements)
references
References 48 publications
5
228
1
3
Order By: Relevance
“…The City of Cape Town is located on the southwestern tip of southern Africa and is situated in the Cape Floristic Region, a globally recognized biodiversity hotspot (Mittermeier et al 2005) and conservation priority (Underwood et al 2009). The city occupies about 2460 km², has a population of 3.7 million people, and includes 19 national terrestrial vegetation types, containing an estimated 3250 plant species, of which 190 are endemic (Rebelo et al 2011, Holmes et al 2012.…”
Section: Study Areamentioning
confidence: 99%
“…The City of Cape Town is located on the southwestern tip of southern Africa and is situated in the Cape Floristic Region, a globally recognized biodiversity hotspot (Mittermeier et al 2005) and conservation priority (Underwood et al 2009). The city occupies about 2460 km², has a population of 3.7 million people, and includes 19 national terrestrial vegetation types, containing an estimated 3250 plant species, of which 190 are endemic (Rebelo et al 2011, Holmes et al 2012.…”
Section: Study Areamentioning
confidence: 99%
“…Temperature and moisture regimes are among the primary elements of terroir (10,11), with growing season temperature being particularly important in delimiting regions suitable for growing wine grapes (Vitis vinifera). Mediterranean climate regions (warm and dry summers; cool and wet winters) are particularly suitable for viticulture (4), while at the same time having high levels of biodiversity, endemism, and habitat loss, making them global biodiversity hotspots (12)(13)(14). Climate change has the potential to drive changes in viticulture that will impact Mediterranean ecosystems and to threaten native habitats in areas of expanding suitability (15).…”
mentioning
confidence: 99%
“…Furthermore, there was a minor difference between the agricultural soil from AL-4 (soybean) and AL-5 (maize), which may be correlated to their crop species. Some studies suggested plant species to be one of major factors influencing the microbial community structure (Calderon et al, 2001;Deangelis et al, 2009;Mendes et al, 2011;Underwood et al, 2009). However, Kielak et al (2008 reported that plant species have only a minor influence on the soil bacterial community composition.…”
Section: Effect Of Different Land-use On Bacterial Community Compositionmentioning
confidence: 99%